2009
DOI: 10.1021/jf902508t
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bile-Acid Binding and Fermentation of High, Medium, and Low Molecular Weight β-Glucan

Abstract: The impact of beta-glucan molecular weight (MW) on in vitro bile-acid binding and in vitro fermentation with human fecal flora was evaluated. beta-Glucan extracted from oat line 'N979-5-4' was treated with lichenase (1,3-1,4-beta-D-glucanase) to yield high (6.87x10(5) g/mol), medium (3.71x10(5) g/mol), and low (1.56x10(5) g/mol) MW fractions. The low MW beta-glucan bound more bile acid than did the high MW beta-glucan (p<0.05). If the positive control, cholestyramine, was considered to bind bile acid at 100%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 34 publications
9
63
1
Order By: Relevance
“…When compared with the SE-HPLC chromatogram of β-glucan reported in our previous study, 26 the SE-HPLC chromatogram of β-glucan in the extract suspension was similar. In our previous study, the β-glucan was extracted from oat flour to have ∼90% purity.…”
Section: ■ Results and Discussionsupporting
confidence: 68%
“…When compared with the SE-HPLC chromatogram of β-glucan reported in our previous study, 26 the SE-HPLC chromatogram of β-glucan in the extract suspension was similar. In our previous study, the β-glucan was extracted from oat flour to have ∼90% purity.…”
Section: ■ Results and Discussionsupporting
confidence: 68%
“…This is in accordance with the in vivo findings of Wolever et al [36] that demonstrated higher cholesterol-lowering effects of oat β-glucan dependent on its molecular weight, and thus its contribution to viscosity. In contrast, Kim et al [37] reported the highest values of bile acid binding for oat fractions containing low molecular weight β-glucan. The authors concluded that other components of the oat fraction might also have contributed to the bile acid binding.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the reduction in DCA and iso-DCA may contribute to the prevention of CRC. One mechanism by which nuts and Synergy1 ® might reduce secondary BA concentrations could be by direct binding of BA by dietary fiber [48,49]. In addition, the SCFA-mediated lowering of pH values in the FS might lead to reduced solubility of secondary BA as well as a reduction in 7α-dehydroxylase activity, which catalyzes the conversion of primary into secondary BA [50].…”
Section: Discussionmentioning
confidence: 99%